Britain : spearhead of attack - Blake, F. Donald
Map showing the UK and Western Europe, indicating the industries characteristic of each area in Britain, and the cities and strategic targets bombed by the R.A.F. in France, Belgium, the Netherlands, Italy and Germany Printed by Alf Cooke Ltd., Leeds and London PO-1810